Imaging mechanotransduction: Seeing forces from molecules to cells. (March 2018) - Fleissner, Frederik; Parekh, Sapun H.
Abstract: Individual cells are constantly exposed to a variety of mechanical stimuli from e.g., arterial pressure, muscle contraction, or changes in mechanics of their supporting tissue. Intense study over the last thirty years has illuminated many intracellular signaling cascades through which mechanical stimuli lead to phenotypic changes in cells and even whole tissues. While much of this work has focused on biochemical and signaling pathway analysis, the recent past has seen quantitative imaging techniques emerge as important tools since they provide the capability to observe local deformations and forces along with changes in cellular physiology. In this review, we briefly discuss recent progress and challenges for two optical imaging approaches: molecular scale and mesoscale force sensing. We conclude by providing an outlook for combining the capabilities of these imaging methods to permit long-term, multiscale mechanotransduction imaging. Graphical abstract: Highlights: Mechanotransduction is a multiscale phenomenon that requires imaging technologies sensitive to many length scales. Molecular scale force sensors have unprecedented access to local forces on single proteins. Mesoscale force mapping can quantify force maps in 3D with high accuracy. Combined molecular and mesoscale force sensing is necessary to visualize the full mechanotransduction process.